A Pro-poor Tourism Case Study: Efate Island, Vanuatu - Watt, Gregory (Auckland University of Technology, 2019)
Vanuatu is classified as a “Least Developed Country” by the United Nations Development Program and is constrained by its socio-economic environment. The majority of Ni-Vanuatu live in a predominantly rural situation, within a traditional cultural environment, and are sustained economically through an informal economy. The minority, constituting 30% at most, work in the formal economy and reside in urban areas. Tourism is the dominant industry on Efate Island with most activity concentrated around the Port Vila locality. Tourism contributes around 88% of the gross earnings to the Efate economy and is seen as the mechanism by which Ni-Vanuatu can transition from their traditional livelihoods into the formal economy. This study concentrates on how the tourism industry could be adjusted to optimise its Pro-Poor performance, while also meeting the future needs of industry. Vanuatu possesses a unique set of characteristics and four basic themes emerge; firstly, how cruise and landed tourism function and interact; secondly, optimisation of landed tourism at a macroscale level to meet future growth; thirdly, enhancement of human capability within the industry; and lastly, how the industry at its various microscale levels fulfils societal and cultural needs of Ni-Vanuatu peoples. The study is primarily exploratory and seeks to establish future areas of research that could contribute to the enrichment of the industry. The scope of the inquiry is purposely broad to enable a whole of industry perspective to be considered. Using a pragmatic paradigm in conjunction with a case study research strategy, a sequential investigation of the tourism industry was carried out to evaluate Pro-Poor characteristics. Commencing with the dual touristic economy the study incorporated a process of funnelling down through consecutive layers of tourism and hospitality, obtaining significant findings. Firstly, while the dual touristic economy based on Cruise and Landed tourism was seen to benefit Vanuatu, they do not co-exist in a complementary fashion, and the former impacts significantly on the later. Unquestionably, Landed visitors are more valuable to the Vanuatu community and should be prioritised. It was found that Ni-Vanuatu would benefit positively if the activity of cruise tourism was more tailored, and systematised around the needs of Landed tourism. Secondly, utilising WTTC figures tourism and hospitality employment was found to be at comparably low levels relative to its contribution to the national economy. With the forecasted growth in the next decade, the lack of adequately trained staff within the industry will escalate. By instituting a “human capability strategy”, there was an opportunity to transition significant numbers of Ni-Vanuatu from the informal economy into the formal economy, while increasing the collective education, skills, and earnings of Ni-Vanuatu working within the industry. Thirdly, an assessment of Vanuatu’s education and Technical and Vocational Education and Training (TVET) capabilities indicates that it is not able to provide the projected numbers of adequately trained staff for tourism’s future needs. There are extremely high rates of unemployment amongst 15-30 year olds and if the TVET capability was built up there is an opportunity to channel young Ni-Vanuatu into positive pathways. However, the required investment in education and TVET, including adequately trained educators is substantial and must be carried out in accordance with a coordinated action plan. Finally, an assessment of the social and cultural characteristics within the industry revealed a number of aspects. Generally, unemployment of females in Vanuatu is higher than males, and they can be marginalised as a consequence. From a Pro-Poor perspective they are preferred within tourism due to their attitude and aptitude in the industry, and significantly, this goes some way to address the national imbalance. Tourism has the potential to be the instigator of Pro-Poor implementations but only if positive action is undertaken. Ultimately, there is a need at governance, industry, and development levels to action strategies in each of the four themed areas.
Keywords: Pro-poor; Pro-poor Tourism; Vanuatu; Port Vila; Efate Island; Progressive pro-poor tourism; Vanuatu tourism capability strategy; Vanuatu tourism training; Vanuatu TVET; Vanuatu Qualifications Authority; VQA; Glocalisation; Vanuatu Glocalisation; Vanuatu cruise tourism; Vanuatu landed tourism